Role of informal carers in medication management for people with long-term conditions: a systematic review - Charlotte Richardson; Laura Lindsey; Maha Alkhaldi (BMJ Open)
Objectives To explore the literature about the role of unpaid informal carers in medication management for people with long-term conditions.Design Systematic review designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Information source MEDLINE (Ovid), Embase (Ovid), PsycINFO, Cumulated Index in Nursing and Allied Health Literature (EBSCO), Scopus and Web of Science were searched from inception until April 2024. Additional papers were identified by searching backwards and forwards the reference lists of included papers.Eligibility criteria Primary research studies were included if they reported medication-related activities undertaken by carers for people with long-term conditions. Qualitative and mixed methods studies were considered without restriction on language or country.Data extraction and synthesis Relevant data were extracted and summarised in a table. The Mixed Method Appraisal Tool was used for quality assessment. Data were narratively synthesised.Results From 12 473 identified records, 107 underwent full text screening and 20 studies were included. Family carers were the predominant type of carer. Spouses and adult children constituted the largest caregiving dyads. Based on the required skills, two groups of roles were identified: physical roles, such as prescription management, and cognitive roles, such as decision-making. Carers used different strategies and tools to undertake medication-related activities including compliance aids and alarms. However, carers reported challenges in their experiences of caregiving, flagging up their need for additional support and education to commence such activities.Conclusion Informal carers undertake a wide variety of medication-related activities. The studies emphasised the need to support families as partners in health outcomes. This systematic review identifies the importance of bridging the gap between carers and healthcare providers. More efforts are needed to empower carers towards better and safer caregiving. Future work could address how to optimise carer involvement and engagement and provide best practice recommendations for carers’ support.PROSPERO registration number CRD42024506694.